L'objet de la DLE - Boyon, Jérôme (Verbum – Analecta Neolatina, 2006)
The paper aims to characterize the reading task as a situation in which it is the communicative reader that leads the dialogue. By formulating hypotheses, the learner poses questions to the text which will answer. In this case, the demarcation between speaking and written language is not pertinent. The prereading tasks also presuppose the validity of the notion of "category" that help reduce the text to a few descriptive parameters. Classroomactivities are arguments that weaken the eclectic and post-communicativist criticisms addressed to the communicative approach by pointing out an non-reducible personality of the learner. Another weak point of these criticisms resides in the history of epistemology. Francis Bacon also plead for a non-reducible personality of the substance and unhappily predicted that chemistry as a science was impossible to be founded.